Model of the Relationship between Workload and Motivation to Employee Performance and Job Satisfaction - Widyatara, Alfina; Waluyo, Minto (Journal La Medihealtico, 2024)
A significant increase in visits, visitor complaints about employees, and turnover rates that exceed the established standards indicate problems related to workload and motivation that will impact employee performance. The purpose of this study was to determine the relationship model of workload and motivation to employee performance and job satisfaction. The method of conducting this research is using a questionnaire with a Google form. The data analysis technique uses Structural Equation Modeling with maximum likelihood estimation (MLE) so that the sample requirements used must meet a minimum of 100 data. Research results at the final stage, namely model modification, obtained the goodness of fit value and cut-off value at chi-square = 176.653, Significance Probability = 0.054, Cmin/df = 1.194, RMSEA = 0.044, GFI = 0.868, AGFI = 0.794, TLI = 0.975, and CFI = 0.982. From the model test results compared to the cut-off value, all indicators have achieved good results, except AGFI. Indicators reach good results (marginal) so that the next analysis test can be continued. Based on the results of hypothesis testing, the results show that workload has a significant effect on employee performance, work motivation has an insignificant effect on employee performance, workload has a significant effect on job satisfaction, work motivation has a significant effect on job satisfaction, and job satisfaction has a significant effect on employee performance.